Deciphering Anthropogenic Effects on the Genetic Background of the Red Deer in the Iberian Peninsula - Queirós, João; Gortázar, Christian; Alves, Paulo Célio (Frontiers in Ecology and Evolution, 2020)
Anthropogenic hybridization is one of the greatest threats to global biodiversity. It incites human-mediated gene flow between non-native/exotic and native taxa, which can have irreversible effects on native species or locally adapted populations, eventually leading to extinction. The red deer, Cervus elaphus, is a game species that, due to its extraordinary economic value, has been introduced in several regions throughout Europe. However, the consequences of those introductions on native populations, namely on their genetic background, have been poorly addressed. This study is focused on the Iberian Peninsula and aims to: i) assess the extent of anthropogenic hybridization/introgression of introduced red deer into the native Iberian populations; ii) evaluate the impact of red deer management regimes on the observed hybridization/introgression patterns; and iii) assess how hybridization/introgression influence the current genetic diversity of native Iberian populations. A set of 11 microsatellites and a 329 bases pair fragment of the mitochondrial D-loop gene were used to estimate nuclear admixture and mitochondrial introgression in 1132 individuals sampled across 46 red deer populations throughout Iberia. A Bayesian approach implemented in the STRUCTURE program was employed to investigate the proportion of admixture between native populations and non-native red deer. Results showed that 17% of individuals presented signs of non-native recent ancestors and 10.1% had non-native mitochondrial haplotypes, reaching an overall hybridization/introgression rate of 23%. Non-native or hybrid individuals were found throughout 40 Iberian red deer populations, and the percentages per population varied between 3.3% and 75.0%, independently of the management regime. Mitochondrial introgression was observed across 15 Iberian red deer populations, being more frequent in free-ranging individuals (16.2%) than in fenced populations (9.2%) but was completely absent from public-owned populations. Nuclear genetic diversity correlated positively with the proportion of hybrid individuals in public-owned populations. The genetic footprint of historical and current human-mediated translocations of non-native red deer into the Iberian Peninsula is evidenced in this study, highlighting the need to implement effective measures to avoid such practices both in Portugal and Spain, in order to preserve the endogenous genetic patrimony of the Iberian red deer populations.